Anesthetic nuances in a hypertrophic cardiomyopathy patient for laparoscopic abdominoperineal resection (Indian Journal of Case Reports, 2019)
Hypertrophic cardiomyopathy is a complex cardiac disease with unique pathophysiologic characteristics and a great diversity of morphologic, functional, and clinical features. It is characterized by a massive asymmetrical hypertrophy of the myocardium. Clinical features range from an absence of symptoms to sudden death. We report a rare case of a 57-year-old male presenting with a history of constipation for 3 months, weight loss and fatigue for 3 months, and blood in stools for 1 month. He was diagnosed with a carcinoma rectum. He was planned for abdominoperineal resection by laparoscopic approach. Aim of this case report is to discuss the challenging technical nuances of anesthetic management of a patient with hypertrophic cardiomyopathy posted for laparoscopic surgery.